2008
DOI: 10.1007/s11248-008-9186-3
|View full text |Cite
|
Sign up to set email alerts
|

Translational fusion of chloroplast-expressed human papillomavirus type 16 L1 capsid protein enhances antigen accumulation in transplastomic tobacco

Abstract: Human Papillomavirus (HPV) is the causal agent of cervical cancer, one of the most common causes of death for women. The major capsid L1 protein self-assembles in Virus Like Particles (VLPs), which are highly immunogenic and suitable for vaccine production. In this study, a plastid transformation approach was assessed in order to produce a plant-based HPV-16 L1 vaccine. Transplastomic plants were obtained after transformation with vectors carrying a chimeric gene encoding the L1 protein either as the native vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
61
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 59 publications
4
61
3
Order By: Relevance
“…For example, cholera nontoxic B subunit (CNTB)-fused native human blood-clotting factor VIII heavy chain (FVIII HC;86.4 kD) or ANGIOTENSIN CONVERTING ENZYME2 (92.5 kD) were expressed at very low levels (Shenoy et al, 2014;Sherman et al, 2014). Likewise, the expression of viral vaccine antigens is quite unpredictable, with high, moderate, or extremely low expression levels (Birch-Machin et al, 2004;Lenzi et al, 2008;Waheed et al, 2011aWaheed et al, , 2011bInka Borchers et al, 2012;Hassan et al, 2014). Furthermore, viral antigens are highly unstable, with expression observed in youngest leaves but not in mature leaves (McCabe et al, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, cholera nontoxic B subunit (CNTB)-fused native human blood-clotting factor VIII heavy chain (FVIII HC;86.4 kD) or ANGIOTENSIN CONVERTING ENZYME2 (92.5 kD) were expressed at very low levels (Shenoy et al, 2014;Sherman et al, 2014). Likewise, the expression of viral vaccine antigens is quite unpredictable, with high, moderate, or extremely low expression levels (Birch-Machin et al, 2004;Lenzi et al, 2008;Waheed et al, 2011aWaheed et al, , 2011bInka Borchers et al, 2012;Hassan et al, 2014). Furthermore, viral antigens are highly unstable, with expression observed in youngest leaves but not in mature leaves (McCabe et al, 2008).…”
mentioning
confidence: 99%
“…In vitro assays of inserted genes with several synonymous codons show that translation efficiency does not always correlate with codon usage in plastid mRNAs (Nakamura and Sugiura, 2007), but they have been used in several codon optimization studies (Lutz et al, 2001;Ye et al, 2001;Franklin et al, 2002;Lenzi et al, 2008;Jabeen at al., 2010;Madesis et al, 2010;Gisby et al, 2011;Wang et al, 2015b;Boehm et al, 2016;Nakamura et al, 2016). While some studies achieved significant increases in expression (75-to 80-fold) after codon optimization (Franklin et al, 2002;Gisby et al, 2011), other studies observed negligible enhancement (Ye et al, 2001;Lenzi et al, 2008;Daniell et al, 2009;Wang et al, 2015b;Nakamura et al, 2016). However, translation initiation and the elongation efficiency of codon-optimized sequences were enhanced when chloroplast gene N-terminal sequences were inserted downstream of 5使 UTRs (Ye et al, 2001;Lenzi et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18 In some cases, the use of a DB (downstream box) was found to be essential for protein accumulation. 19 Lenzi et al 19 showed that the HPV 16 L1 capsid protein accumulated up to 1.5% TSP only when vectors carried a TCR formed by the 5'-UTR and first 42 nucleotides of the plastid rbcL gene. The importance of the DB region as regulator of protein production has been confirmed recently by Gray et al 20 that demonstrated that an efficient DB fusion allowed high-level accumulation of bacterial 尾-glucosidase in transgenic tobacco plastids.…”
Section: Protein Accumulationmentioning
confidence: 99%
“…Major advantages of plant-made pharmaceuticals include low cost of production, higher scale-up capacity and lack of risk of contamination with mammalian pathogens. Several antigenic proteins have been produced in plant, examples are plant-made vaccines against smallpox, HIV and HPV (Human Papilloma Virus) (Lenzi et al, 2008;Rigano et al, 2009;Scotti et al, 2009). In addition, transgenic plants can represent a suitable vehicle for oral delivery of pharmaceuticals since the plant cell wall protects the recombinant antigen in the harsh condition of stomach and intestine (Sharma et al, 2008a).…”
Section: Production Of Pharmaceutical Proteinsmentioning
confidence: 99%